Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
Answer:
0 = 4x
Step-by-step explanation:
-2(2 - 2x) = 4 - 8(1 - x)
-4 + 4x = 4 - 8 + 8x
-4 + 4x = -4 + 8x
-4 + 4 = 8x - 4x
0 = 4x
Answer:
0=4x
Step-by-step explanation:
You can read this problem as simplify -2(2-2x)=4-8(1-x), because being equivalent to something can be started with simplification.
So now, on to the simplification now:
-2(2-2x)=4-8(1-x)
Step 1: Open Parantheses -4+4x=4-8+8x
(Remember, two negatives equal a postitive. That's why you get 4x and 8x, not -4x nor -8x.)
Step two: Tidy (Put x's on one side, others on the other.) 4x-8x=4-8+4
(Remember, when you move a number/variable to one side, the negative/positive sign becomes the opposite.)
Step three: Solve -4x=0
Now, be get -4x=0. But then again, if -4x=0, then 4x=0, considering x will be zero.
I hope you liked this explanation! If you have more problems, I'm always free to help.
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.